Analysis of The Internal Control System and The Role of The Internal Auditor in Optimizing Hospital Performance - Asfeni Nurullah; Tertiarto Wahyudi; Aspahani (Nusantara Science and Technology Proceedings, 2020)
Hospital performance is an important factor in measuring its success rate. Hospitals need an internal control system and internal auditors that are able to optimize hospital performance. This study aims to determine the effect of the internal control system and the role of internal auditors in optimizing hospital performance. This study is a mix methods study between qualitative and quantitative research. The research data uses primary and secondary data types which are collected through two techniques, namely field research and library research. The population of the study was all hospital employees. The research sample includes 110 employeesthe medical department, the paramedic section, the medical support section, and the general department in the hospital. The data analysis method uses the product moment correlation analysis technique. The results show that the internal control system has a positive and significant impact on hospital performance. This shows that the better Internal Control, the better the Hospital Performance. Meanwhile, the role of internal auditors has a positive and significant impact on hospital performance. This means that the increasing quality of the Internal Auditor owned by an auditor greatly influences the Hospital's performance, it will increase public confidence regarding the financial statements that will be audited by an independent auditor.